A política dos eleitores no Facebook dos candidatos: uma análise de dispositivos interacionais construídos nas eleições presidenciais de 2014 - Maia, Lídia Raquel Herculano (Universidade do Vale do Rio dos Sinos, 2019)
The 2014 Brazilian presidential election was marked by the intensity of the dispute, along with an intense process of political conversation on social networks and on the streets. In that context, our research focuses on the interactional processes that took place on the Facebook pages of the three main presidential candidates: Dilma Rousseff (PT), Aécio Neves (PSDB) and Marina Silva (PSB). The aim of this research is to understand the interactional logics developed from the participation of electors-commenters and campaign staffs on the dispositif “candidate's page” on Facebook. Through qualitative empirical research, we adopted an ethnomethodological perspective allied to analytical abductive reasoning to search and assemble evidence that allowed us to develop inferences for the construction of the research case. In theoretical terms, we discuss the assumptions surrounding political campaigns and online political conversation; the concepts of mediatization, social fields, circuits and circulation; the transformation of public space in the mediatized society context; and factual issues and theoretical interpretations about the social network Facebook. In the second part of the thesis, the inferences formulated from the work with the empirical data are presented, starting with the contextualization of the scenario of the 2014 elections and their repercussions. From three systematizing perspectives, the singularities of the research case are explored at the following levels: 1) descriptive and procedural, in which the dispositif “candidate's page” is characterized individually due to its more immediate elements; 2) inferential, in which the interactional logics, evidenced in each page, are articulated in the form of organizing axes of the speeches and political-interactional actions of candidates and electors; 3) theoretical model, in which a joint apprehension of the descriptions and analyses previously presented is developed from the conceptual perspective of “circulation”. The analysis of the empirical object led us to realize how the pages of the candidates have been transformed into spaces of strengthening of links (between electors and politicians), clashes, public discussion and sharing of feelings and affections.

Las elecciones presidenciales brasileñas de 2014 fueron marcadas por la vehemencia de la disputa, acompañado de un intenso proceso de conversación política en las redes y en las calles. En ese contexto, esta investigación se concentra en los procesos interaccionales desarrollados en las páginas de Facebook de los tres principales candidatos a la presidencia: Dilma Rousseff (PT), Aécio Neves (PSDB) y Marina Silva (PSB). El objetivo de la investigación consiste en entender las lógicas interaccionales que se desarrollan en la participación de los electores-comentadores y de los equipos de campaña en el dispositivo “página del candidato” en Facebook. A partir de una investigación empírica de abordaje cualitativo, seguimos la propuesta etnometodológica aliada al razonamiento analítico abductivo para buscar indicios que, articulados, nos permitiesen elaborar inferencias para la construcción del caso de la investigación. En términos teóricos, discutimos: los presupuestos que involucran campañas políticas y la conversación política online; los conceptos de mediatización, campos sociales, circuitos y circulación; la transformación del espacio público en el contexto de la sociedad en mediatización; y cuestiones factuales e interpretaciones de naturaleza teórica sobre la red social Facebook. En una segunda parte de la tesis, son presentadas las inferencias formuladas a partir del trabajo con los datos empíricos, iniciando con la contextualización del escenario de las elecciones de 2014 y sus desdoblamientos. A partir de tres perspectivas de sistematización, las singularidades del caso de investigación son exploradas en los siguientes niveles: 1) descriptivo y procesal, en el cual el dispositivo “página del candidato” es caracterizado individualmente en función de sus procesos y elementos más inmediatos; 2) inferencial, en el cual las lógicas de interacción, evidenciadas en cada página, son articuladas en forma de ejes organizadores de los discursos y acciones político-interaccionales de los candidatos y electores; 3) y de modelo teórico, en el cual se busca una aprehensión conjunta de las descripciones y análisis anteriormente presentados, a partir de la perspectiva conceptual de la “circulación”. El análisis del objeto empírico nos condujo a la percepción de cómo las páginas de los candidatos se transformaron en espacios de refuerzo de vínculos (entre electores y políticos), de confrontaciones, discusión política, así como también de sentimientos y afectos compartidos.
Keywords: Eleições Presidenciais de 2014; Página do Candidato no Facebook; Circulação; Dispositivo Interacional; Conversação Política Online; 2014 Brazilian Presidential Elections; Candidate’s Page on Facebook; Circulation; Interactional Dispositif; Online Political Conversation; Elecciones Presidenciales de 2014; Página del Candidato en Facebook; Circulación; Dispositivo Interaccional; Conversación Política Online; ACCNPQ::Ciências Sociais Aplicadas::Comunicação